Patient-specific responses to SMN2 splice-modifying treatments in spinal muscular atrophy fibroblasts - Ilaria Signoria; Maria M. Zwartkruis; Lotte Geerlofs; Elena Perenthaler; Kiterie M.E. Faller; Rachel James; Harriet McHale-Owen; Jared W. Green; Joris Kortooms; Sophie H. Snellen; Fay-Lynn Asselman; Thomas H. Gillingwater; et al. (Molecular Therapy: Methods & Clinical Development)
The availability of three therapies for the neuromuscular disease spinal muscular atrophy (SMA) highlights the need to match patients to the optimal treatment. Two of these treatments (nusinersen and risdiplam) target splicing of SMN2, but treatment outcomes vary from patient to patient. An incomplete understanding of the complex interactions among SMA genetics, SMN protein and mRNA levels, and gene-targeting treatments, limits our ability to explain this variability and identify optimal treatment strategies for individual patients. To address this, we analyzed responses to nusinersen and risdiplam in 45 primary fibroblast cell lines. Pre-treatment SMN2-FL, SMN2Δ7 mRNA, and SMN protein levels were influenced by SMN2 copy number, age, and sex. After treatment, SMN and mRNA levels were more heterogeneous. In 43% of patients, response to both therapies was similar, but in 57% one treatment led to a significantly higher SMN increase than the other treatment. Younger age, higher SMN2 copy number, and higher SMN levels before treatment predicted better in vitro efficacy. These findings showcase patient-derived fibroblasts as a tool for identifying molecular predictors for personalized treatment.